UV Spectrophotometric Method for Determination of Cinitapride in Pure and its Solid Dosage Form - B. Thangabalan; A. Elphine Prabahar; R. Kalaichelvi; P. Vijayaraj Kumar (E-Journal of Chemistry)
A new, rapid, precise, accurate and sensitive analytical method was developed for the UV spectrophotometric assay of cinitapride (CTP). The drug obeyed the Beer's law and showed good correlation. It showed absorption maxima at 260 nm in methanol. The linearity was observed between 5-40 µg mL-1. The results of analysis were validated by recovery studies. The recovery was more than 99%. The proposed method is the only method available for spectrophotometric determination of the drug. It is simple, precise, sensitive and reproducible and can be used for the routine quality control testing of the marketed formulations.